Problem-Based Learning Model in Classroom Management with Scaffolding Techniques on Learning Outcomes and Student Independence - Sabil, Husni; Asrial, Asrial; Syahrial, Syahrial; Kiska, Nurul Delima; Saputri, Juwita; Damayanti, Latipia; Luthfiah, Qonita; Silvia, Ninda (International Journal of Elementary Education, 2021)
There are still many students who get scores below the average. It is because students have difficulty in learning. This study examines the effect of problem-based learning models with scaffolding techniques, the effect of independent learning on student learning outcomes, and the level of differences in learning outcomes between students who apply problem-based learning models and problem-based learning models with scaffolding techniques rather than conventional learning models. This study uses a quantitative research type with a quasi-experimental design with a 3 x 3 factorial design, using a Nonequevalent control group design (pretest-posttest). The sample in this study amounted to 77 students. The study was conducted using quantitative data obtained from questionnaires and surveys. The instrument used to collect data is a questionnaire. The techniques used to analyze the data are qualitative descriptive analysis, quantitative, and inferential statistics. The study results are significant differences between the Problem Based Learning learning model with the Scaffolding technique with the conventional learning model of student independence in learning, and student learning outcomes are dominant in the application of problem-based learning. It can be concluded that the application of the Problem Based Learning model with the Scaffolding technique obtains the best learning outcomes when compared to other learning models.